Implementation of Engineering Everywhere in Physics LKPD Based on STEM Approach to Improve Science Process Skills - Zainuddin Zainuddin*; Muhammad Syukri; Soni Prayogi; Safira Luthfia (Universitas Syiah Kuala, 2022)
High school students (MAN 3) Banda Aceh are experiencing problems related to science process skills, so they need to be improved. Efforts to improve KPS can be pursued through